2008
DOI: 10.1681/asn.2007080916
|View full text |Cite
|
Sign up to set email alerts
|

KIBRA Modulates Directional Migration of Podocytes

Abstract: Asymmetric delivery and distribution of macromolecules are essential for cell polarity and for cellular functions such as differentiation, division, and signaling. Injury of podocytes, which are polarized epithelial cells, changes the dynamics of the actin meshwork, resulting in foot process retraction and proteinuria. Although the spatiotemporal control of specific protein-protein interactions is crucial for the establishment of cell polarity, the mechanisms controlling polarity-dependent differentiation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
142
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(150 citation statements)
references
References 47 publications
7
142
1
Order By: Relevance
“…This upstream regulator of Hippo pathway (40)(41)(42) controls the activity of the transcriptional coactivator YAP through its interaction with large-tumor suppressor kinase 1 (LATS1) and LATS2 kinases (42). Alongside these characterized functions in Hippo signaling, recent studies have revealed a role for KIBRA in cell migration and polarization (43)(44)(45). Overexpression of KIBRA can inhibit migration of MCF10A cells (44).…”
Section: Overexpression Of Kibra Rescues the Migration And Adhesionmentioning
confidence: 99%
“…This upstream regulator of Hippo pathway (40)(41)(42) controls the activity of the transcriptional coactivator YAP through its interaction with large-tumor suppressor kinase 1 (LATS1) and LATS2 kinases (42). Alongside these characterized functions in Hippo signaling, recent studies have revealed a role for KIBRA in cell migration and polarization (43)(44)(45). Overexpression of KIBRA can inhibit migration of MCF10A cells (44).…”
Section: Overexpression Of Kibra Rescues the Migration And Adhesionmentioning
confidence: 99%
“…Two studies have investigated KIBRA signaling in podocytes. The first, by Duning et al (14) in 2008, identified KIBRA's presence in podocytes of the glomerular tuft and in renal tubular cells. This study demonstrated that KIBRA interacts with the actin-bundling protein synaptopodin and the cell polarity protein PATJ.…”
Section: Glomerulusmentioning
confidence: 99%
“…KIBRA was originally identified as a memory performance-associated protein in humans (28 -32), and this function was recently confirmed in mice (33). The physiological function of KIBRA in non-neuronal cells is much less defined, although KIBRA has been shown to be involved in cell migration in podocytes (34) and NRK cells (35) and in epithelial cell polarity (36). KIBRA also interacts with the motor protein dynein light chain 1 to positively regulate cell growth in breast cancer cells (37).…”
mentioning
confidence: 99%